Kerangka Pengembangan Kurikulum dalam Konteks Pendidikan Abad ke-21 dan Implementasinya pada Kurikulum Merdeka di Indonesia - Muh. Abid Mustahar AM; Siti Arah Suniyah; Suhardi; Sirajuddin Saleh (Jurnal Neo Societal, 2025)
This research aims to describe the curriculum development framework as an effort to improve the quality of education that is relevant to the demands of the 21st century. This study uses a qualitative research method with a library research approach, which is by analyzing various literature sources such as books, journals, and scientific articles related to curriculum development theory and practice. The results of the study show that curriculum development is a systematic and continuous process that involves needs analysis, goal formulation, design, implementation, and evaluation. The foundation of curriculum development includes philosophical, psychological, socio-cultural, and scientific aspects, with the principles of relevance, flexibility, effectiveness, and efficiency. Several models such as Tyler, Taba, Oliva, Saylor-Alexander, Beauchamp, and Bruner are important references in designing a curriculum that is adaptive to change. In the Indonesian context, the Independent Curriculum is a form of actualization of curriculum development that emphasizes differentiated learning, strengthening the Pancasila Student Profile, and implementing project-based learning to face global challenges. Thus, the curriculum development framework plays an important role in shaping a dynamic, relevant, and competency-oriented education system for the future.